JUDICIAL REVIEW OF DECISIONS OF POLYGAMIC POLICY IN SEMARANG RELIGIOUS COURT - Peni Rinda; Achid Ulfi Sukriya (Jurnal Pembaharuan Hukum, 2017)
Polygamy is a problem in marriages that is often discussed. Polygamy marriage as regulated in the polygamous marriage law, it is under the principle of monogamy which is not actually the absolute monogamous principle, but it is also called the principle of open monogamy. In the Compilation of Islamic Law (KHI) polygamy is the permission for a husband to have more than one wife on certain conditions. The method used in this legal research was sociological juridical approach that is the juridical review of the judge's verdict on polygamy permit in the Religious Courts of Semarang. The basic consideration to create the benefit of the people is that the active role of the Religious Court judges interpret the law in actual in order to apply the existing law in accordance with the needs of the development of society to achieve the mutual benefit. Elements in the principle of mutual benefit is not only the principle of legal certainty, but in the consideration there must also be the principle of benefit and the principle of justice